Short-term memory in hearing-impaired and hearing children between 13 and 15 years of age - Mildner, Vesna (Array, 2012)
The data on the differences between hearing impaired and hearing individuals on short-term memory tasks are inconclusive. Whereas there is ample literature providing evidence that the hearing subjects outperform their hearing-impaired peers on various digit span, memory span, phonemic awareness and similar tests (see Koo et al., 2008, for review and original data) there are some authors who claim that the need for speech understanding under difficult conditions, i.e. in cases of hearing impairment, enhances working memory capacity in order for it to make up for the adverse processing situation (e.g. Lyxell, et al., 2003). In any case, results have been shown to be affected by the mode of stimuli presentation (visual or auditory) and stimuli properties (abstract vs. concrete nouns ; rate of presentation), subjects' preferred channel of everyday communication (signing, oral, cued), age, and a host of other factors (Conway et al., 2005 ; Koo et al., 2008). Any teacher working with hearing impaired children of school age will agree that their short-term memory and, similarly (but not to be taken quite synonymously), their working memory, seem to be of smaller capacity and less flexible than is the case with hearing children of comparable age and educational context. Manifestations are most obvious in but not limited to their reading skills. The aim of this study was to test short-term memory in hearing-impaired elementary school children (7th and 8th –graders ; N = 18) and 18 hearing controls from a local elementary school, matched for age and school grade. The hearing-impaired children all attend a special elementary school for the hearing impaired where they are expected to master the same program that is prescribed by national educational authorities, as their hearing peers. The differences in the groups’ treatment are in the fact that the hearing impaired work in small groups and in addition to their regular curriculum have continuous oral rehabilitation (based on verbotonal method). We applied several word-recall tests: (1) Fast recall tests: 4 lists, each consisting of 10 words presented at the rate of one per second in block letters on computer screen. On 2 tests the children were asked to rehearse the words sub-vocally, and on 2 no sub- vocalization was required. On (2) Medium and (3) Slow recall tests, the same design was applied but the rate of word presentation was 1, 5 s and 2 s, respectively. In each list, the words were balanced for concreteness/abstractness. Rate of presentation and sub-vocalization instructions were balanced across lists. Preliminary results indicate that the rate of presentation and sub- vocalization instructions affect the outcome of word recall, so that at the fastest rate of presentation and at the slowest rate without sub- vocal rehearsal the results are the poorest in the hearing impaired group.